2013
DOI: 10.1186/2052-4374-25-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diabetes Mellitus with a Combination of Vitamin D Deficiency and Arsenic Exposure in the Korean General Population: Analysis of 2008–2009 Korean National Health and Nutrition Examination Survey Data

Abstract: ObjectivesWe present data from the Korean National Health and Nutritional Examination Survey (KNHANES) 2008–2009 on the combination of vitamin D deficiency and arsenic exposure on diabetes mellitus (DM) in a representative sample of the adult Korean population.MethodsThis study was based on data obtained from the KNHANES 2008–2009, which was conducted for 3 years (2007–2009) using a rolling sampling design that involved a complex, stratified, multistage, probability-cluster survey of a representative sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…Thus, the present study suggested that vitamin D status had no association with GDM preva- .4 nmol/L). Surprisingly, the levels in the first trimester were much lower than 40.363.4 nmol/L in 20-to 39-y-olds compared to levels reported by KHANES 2008KHANES -2009, and then they increased to more than the average levels of a Korean population (7). In the present study, low levels of serum 25-OH-D levels in the first trimester were related to a low intake of vitamin D. Daily vitamin D intake was calculated from food frequency tests that listed foods containing meaningful amounts of vitamin D. Frequencies of consuming each food and corresponding vitamin D intakes were calculated for each subject from these results using CAN-PRO (Korean Nutrient Society, Seoul, Korea).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Thus, the present study suggested that vitamin D status had no association with GDM preva- .4 nmol/L). Surprisingly, the levels in the first trimester were much lower than 40.363.4 nmol/L in 20-to 39-y-olds compared to levels reported by KHANES 2008KHANES -2009, and then they increased to more than the average levels of a Korean population (7). In the present study, low levels of serum 25-OH-D levels in the first trimester were related to a low intake of vitamin D. Daily vitamin D intake was calculated from food frequency tests that listed foods containing meaningful amounts of vitamin D. Frequencies of consuming each food and corresponding vitamin D intakes were calculated for each subject from these results using CAN-PRO (Korean Nutrient Society, Seoul, Korea).…”
Section: Discussioncontrasting
confidence: 57%
“…Serum levels of 25-hydroxyvitamin D (25-OH-D), a good measure of vitamin D status in humans, are inversely related to hypertension, diabetes, carotid atherosclerosis, myocardial infarction, congestive heart failure, stroke, microalbuminuria, and kidney dysfunction (3)(4)(5)(6). In a recent cross-sectional study on a Korean population, women less than 50 y old with more serum 25-OH-D (75 nmol/L) had a significantly lower prevalence of type 2 diabetes than those with less 25-OH-D (25 nmol/L) (7). In addition, serum 25-OH-D levels were significantly negatively associated with fasting insulin and homeostatic model assessment for insulin resistance (HOMA-IR) values in all participants.…”
mentioning
confidence: 99%
“…Epidemiological studies have reported an association between arsenic exposure and T2DM [ 87 , 90 , 92 , 94 , 170 ].…”
Section: Environmental Chemicalsmentioning
confidence: 99%
“…β -glucan mainly reduces insulin resistance to improve glucose metabolism [34]. Koreans have low levels of 25-OH-cholecalciferol in the blood, indicating vitamin D insufficiency that may affect glucose homeostasis with decreasing lean body mass [35,36]. Therefore, the combination of aronia, ginseng and mushroom may have a potent ant-diabetic activity.…”
Section: Discussionmentioning
confidence: 99%